Q-Curvature, Spectral Invariants, and Representation Theory - Branson, T.P. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We give an introductory account of functional determinants of elliptic operators on manifolds and Polyakov-type formulas for their infinitesimal and finite conformal variations. We relate this to extremal problems and to the Q-curvature on even-dimensional conformal manifolds. The exposition is self-contained, in the sense of giving references sufficient to allow the reader to work through all details.